Technical Considerations in Remote LIMS Access via the World Wide Web. Issue 4 (11th December 2005) - Ulma, William; Schlabach, David M.
Abstract : The increased dependency on the World Wide Web by both laboratories and their customers has led LIMS developers to take advantage of thin-client web applications that provide both remote data entry and manipulation, along with remote reporting functionality. Use of an LIMS through a web browser allows a person to interact with a distant application, providing both remote administration and real-time analytical result delivery from virtually anywhere in the world. While there are many benefits of web-based LIMS applications, some concern must be given to these new methods of system architecture before justifying them as a suitable replacement for their traditional client-server systems. Developers and consumers alike must consider the security aspects of introducing a wide area network capable system into a production environment, as well as the concerns of data integrity and usability.